2019
DOI: 10.1175/jcli-d-18-0670.1
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variation of Precipitation over the Hengduan Mountains during Rainy Seasons

Abstract: The present study investigates the interdecadal variation of precipitation over the Hengduan Mountains (HM) during rainy seasons from various reanalysis and observational datasets. Based on a moving t test and Lepage test, an obvious rainfall decrease is identified around 2004/05. The spatial distribution of the rainfall changes exhibits large and significant precipitation deficits over the southern HM, with notable anomalous lower-level easterly divergent winds along the southern foothills of the Himalayas (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 83 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…It means that these two typical circulation patterns are responsible for extreme precipitation over southern China, but the affected regions vary with their different locations/phases. In addition, it was reported that SRP can influence rainy-season mean rainfall over SWC in interannual and interdecadal time scale (D. H. Dong et al, 2018Dong et al, , 2019. We calculate the SRP index before and after the REPEs, following Hong and Lu (2016) to investigate whether the two Rossby wave trains in the paper are related to SRP.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that these two typical circulation patterns are responsible for extreme precipitation over southern China, but the affected regions vary with their different locations/phases. In addition, it was reported that SRP can influence rainy-season mean rainfall over SWC in interannual and interdecadal time scale (D. H. Dong et al, 2018Dong et al, , 2019. We calculate the SRP index before and after the REPEs, following Hong and Lu (2016) to investigate whether the two Rossby wave trains in the paper are related to SRP.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Under the background of global warming, the daily precipitation extremes in SWC are sensitive to anthropogenic influences (H. P. Chen & Sun, 2017). From an interdecadal perspective, the precipitation variability over SWC is influenced by the Indian summer monsoon (ISM), East Asian summer monsoon (EASM), the Silk Road pattern (SRP), and sea surface temperature (SST) over Indian Ocean, tropical‐North Pacific Ocean, and so on (D. H. Dong et al., 2019; L. Liu, Cao et al., 2011; L. Wang, Huang et al., 2018; T. Wei et al., 2018). The interannual variability of precipitation over SWC is also attributed to the variability of the ISM and EASM (X.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 151 stations in HM are selected for analysis. The rainy seasons of HM are from May to September, and the total precipitation during rainy seasons accounts for more than 80% of annual total precipitation (Gao et al ., 2013; Dong et al ., 2018; Dong et al ., 2019; Tao et al ., 2020). Besides, monthly global land‐surface precipitation dataset based on rain gauges from the Global Precipitation Climatology Centre Full Data Reanalysis Version 6.0 (GPCC V6; Schneider et al ., 2014) with a spatial resolution of 0.5° × 0.5° is used to verify its consistency with station observations.…”
Section: Methodsmentioning
confidence: 99%
“…The variables include precipitation, evaporation, horizontal winds, vertical pressure velocity, specific humidity, surface pressure, air temperature, and geopotential height. According to the results of our previous studies, JRA55 well capture the climatology (Tao et al ., 2020), interannual (Dong et al ., 2018), and interdecadal (Dong et al ., 2019) characteristics of HM precipitation. The monthly SST data is from NOAA Extended Reconstructed Sea Surface Temperature (ERSST) V5 on a 2° × 2° grid (Smith and Reynolds, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation